2021
DOI: 10.32529/glasser.v5i2.1038
|View full text |Cite
|
Sign up to set email alerts
|

Pembentukan Karakter Religius, Gemar Membaca, Dan Tanggung Jawab Pada Anak Sekolah Dasar

Abstract: Pendidikan keluarga merupakan Lembaga Pendidikan yang pertama, proses pembentukan karakter-karakter terjadi akibat dari pembiasaan. Pembentukan kebiasaan akan lebih efektif bila didukung oleh sosok teladan yang dapat dijadikan panutan dalam kehidupan keluarga. Tujuan penelitian ini adalah untuk mendeskripsikan tentang pembentukan karakter gemar membaca, karakter religius dan tanggung jawab pada anak usia sekolah dasar. Metode penelitian menggunakan pendekatan deskriptif kuantitatif. Teknik pengumpulan data dil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Sikap ini membangun karakter saling menghargai (Widiastiti & Sumantri, 2020). Pembangunan karakter dalam anak usia sekolah dasar sangat penting karena akan melekat pada siswa selamanya (Hidayati et al, 2021).…”
Section: Pretestunclassified
“…Sikap ini membangun karakter saling menghargai (Widiastiti & Sumantri, 2020). Pembangunan karakter dalam anak usia sekolah dasar sangat penting karena akan melekat pada siswa selamanya (Hidayati et al, 2021).…”
Section: Pretestunclassified
“…The values of local wisdom will help students understand every concept in the material so that they gain knowledge, but they can also practice it outside of school. In a study, (Hidayati et al, 2021) suggested that in order to strengthen Indonesian local character learning, the values of local wisdom must be increased in character learning. In this case, Faiz and Soleh (2021) found one of the characters that grows and develops to create creative abilities in sustaining life through entrepreneurial activities.…”
Section: The Term Of Local Wisdom In Learning Cycle Managementmentioning
confidence: 99%
“…From the data above, 25 students have responded to the question and the results are 100% of students answered yes, that they have implemented and used to say goodbye and shake hands with parents or guardians at home before leaving for school (Hukum et al, 2017;Hidayati et al, 2021). And here as educators, we must continue to invite and continue to protect children that it is important to do every time they want to go.…”
Section: Figure 2 Shaking Hand Before Going To Schoolmentioning
confidence: 99%
“…Research on the formation of religious characters has been conducted by (Hidayati et al, 2021) in Kudus which revealed that forming religious characters by inserting religious content in literacy activities, especially reading activities. Likewise, the findings (Imansyah, 2020) state that religious characters that are formed consistently give results in the form of the formation of an orderly attitude, courtesy, mutual respect, accustomed to saying greetings and sorry, praying in congregation, dhikr, sholawat, discipline to pray before and after learning, read the Qur'an every time they enter class.…”
Section: Figure 10 Implementing Du'amentioning
confidence: 99%
See 1 more Smart Citation